A Response: Threshold Concepts in Religious Education and Theology. Issue 2 (2nd July 2016) - Rymarz, Richard
Abstract : This paper presents a response to other contributions in this volume on the theme of using threshold concepts in religious education. It draws together some common threads that have emerged in this volume and notes the value of using threshold concepts, especially in certain context areas. It also provides a sense of the future of threshold concepts in religious education as well as some of the ongoing and emerging challenges in this area such as ensuring that classroom practice reflects what is proposed in the curriculum both for schools with religious affiliation and public schools. In Quebec, for instance, in very recent times the province has introduced a mandatory course in ethics and religious culture. This is an extremely ambitious programme with a wide range of proposed topics such as the nature of secularity and its impact on religious worldview and, perhaps the most complex, better understanding of indigenous religions.